Think Big for Reuse. - WITMAN, PAUL D.; RYAN, TERRY (Communications of the ACM, 2010)
The article discusses the topic of large-grained reuse of computer software, using the example of a international financial corporation which successfully reused components of its internet banking services, automatic teller machine (ATM) software, and network management tools. In particular, three Java applications are studied, involving international financial message systems, portal services, and alert capabilities. The principle of layered computer architecture is said to be helpful in this context, as is the pragmatic use of compatible code sets.